RESEARCH ARTICLE: IMPACT OF THE COVID-19 PANDEMIC ON INTERNATIONAL CONFLICTS: IN THE CASE OF THE TRANSNISTRIAN CONFLICT - Yusupov Shakhzod (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The article is devoted to the current aspects of the relations between the parties in the process of resolving disputes in the context of the COVID-19 pandemic. Based on the Transnistrian conflict, it can be seen that the parties to the conflict not only changed their positions and did not stop the conflict, but also made actions that aggravated the situation. This article analyzes the new restrictive measures taken by Moldova against the Transnistrian region and comments on how relations between the parties to the conflict will develop after the end of the pandemic. As in dozens of other modern conflicts, in the conditions of the pandemic, the conflict in the Moldova-Dniester conflict did not subside, but new conflicts arose: increased social tension, diversion of forces and attention from the current order of political and diplomatic negotiations, reversing the sides from the process of conflict resolution.